(untitled) (Journal of the College of Basic Education, 2026)
This research aims to explore the opposing dualities in the novel (The wine) by Iraqi novelist Anam Kachachi, who has produced numerous literary and narrative works and become a literary icon. The researcher attempts to investigate and analyze an artistic and expressive phenomenon revealed by the novel.